2020
DOI: 10.1007/s11606-020-05670-z
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Scale for Screening Lower-Extremity Arterial Disease as a Possible Cause of Low Back Pain: a Cross-sectional Study Among 542 Subjects

Abstract: BACKGROUND: Epidemiological, imaging, and anatomical studies suggest an association between proximal arterial atherosclerosis and development of low back pain (LBP). OBJECTIVES: We aimed to define (1) the frequency and (2) factors associated with exercise-induced proximal ischemia (EIPI) in individuals with LBP and (3) develop a clinical screening scale. DESIGN: Monocentric cross-sectional study. PARTICIPANTS: All patients with history of ongoing LBP referred to our exercise investigation laboratory for exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…Most of the analyzed studies are of the observational type carried out through questionnaires, where a direct correlation was observed with the increased risk of developing cardiovascular disease in individuals with chronic pain, a direct relationship between the intensity of the pain and the severity of the cardiovascular symptoms, and individuals with cardiovascular disease who did not present with pain showed a better prognosis [45][46][47]49,51,[53][54][55][56][58][59][60][61][62][63][64].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the analyzed studies are of the observational type carried out through questionnaires, where a direct correlation was observed with the increased risk of developing cardiovascular disease in individuals with chronic pain, a direct relationship between the intensity of the pain and the severity of the cardiovascular symptoms, and individuals with cardiovascular disease who did not present with pain showed a better prognosis [45][46][47]49,51,[53][54][55][56][58][59][60][61][62][63][64].…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar disc herniation caused by degenerative lumbar disc disease is a common reason of low back pain 4 . Lumbar lordosis (LL) is one of the four physiological curvatures of the spine.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have focused on lower limbs rehabilitation protocol with walking or mixed training programs [8,11] (both aerobic and resistance), but information about muscular pain/retraction is still missing. In fact, clinical practice has suggested that a lot of patients suffer pain in the lumbar region associated with a retraction of the muscles [12]. This framework is probably a driver toward claudication [13]: calf muscles stiffness reduces, for example, the ankle dorsal flexion and then increases the risk of fall during the clearance of the feet [14].…”
Section: Introductionmentioning
confidence: 99%